1998
DOI: 10.1088/0953-4075/31/13/017
|View full text |Cite
|
Sign up to set email alerts
|

Electron-impact single ionization of low-charged titanium ions

Abstract: The electron-impact single ionization of low-charged Ti ions was studied both experimentally and theoretically. Absolute cross sections for Ti q+ ions in charge states q = 1 to 6 except 3 were measured using a crossed-beams technique as well as calculated with the configuration-average distorted-wave method, including both direct ionization and excitationautoionization contributions. For charge states q = 4, 5 and 6, the measurements are in good agreement with the calculations considering that large components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Metastable levels in the ion beam have been a significant problem in systems isoelectronic to Fe 8+ , such as in the measurements of Ti 4+ [28], Cr 6+ [29], and Ni 10+ [30]. The measurement of the isoelectronic ion Mn 7+ by [31] does not contain an obvious signal from metastables, but Dere [10] found that the cross section was much larger than predicted by theory and so considered the cross section to be unreliable.…”
Section: Metastablesmentioning
confidence: 99%
“…Metastable levels in the ion beam have been a significant problem in systems isoelectronic to Fe 8+ , such as in the measurements of Ti 4+ [28], Cr 6+ [29], and Ni 10+ [30]. The measurement of the isoelectronic ion Mn 7+ by [31] does not contain an obvious signal from metastables, but Dere [10] found that the cross section was much larger than predicted by theory and so considered the cross section to be unreliable.…”
Section: Metastablesmentioning
confidence: 99%
“…However, a knowledge of titanium data is necessary for titanium-endowed carbon surfaces for fusion reactors (Janev 1993). Electronimpact single-ionization cross sections have been measured for ions in charge states q = 1-6 (Falk et al 1983, Mueller et al 1985, Diserens et al 1988, Chantrenne et al 1990, Hartenfeller et al 1998. In this paper we report on our recent investigations for the electron-impact double, triple and quadruple ionization of low-charged titanium ions.…”
Section: Introductionmentioning
confidence: 95%
“…Absolute cross sections were obtained by employing the dynamic crossed-beams technique (Müller et al 1985), where the electron gun is moved up and down through the ion beam with simultaneous registration of the ion signal and both actual beam currents. The total experimental uncertainties of the measured cross sections are typically 8% at the maximum resulting from the quadrature sum of the non-statistical errors of about 7.8% and the statistical error at 90% confidence level (Hartenfeller et al 1998).…”
Section: Experimental Techniquementioning
confidence: 99%
“…Pindzola et al 1987, Griffin andPindzola 1988). Also, experimental cross section data for these metallic impurities of several isonuclear sequences have been measured (Gregory et al 1986, Stenke et al 1995a, 1995c, 1999, Hathiramani et al 1996, Hartenfeller et al 1998, Shaw et al 2001. Aluminium alloys are also a component of a fusion device and therefore its impurities can lead to energy loss in the hot plasma region by radiative cooling.…”
Section: Introductionmentioning
confidence: 99%